An investigation into resilience strategies in the medical tourism supply chain - Elham Mohammadipour; Esmaeil Mazroui Nasrabadi (Tourism)
The present study has adopted a mixed method approach to investigate the risks occurring in the supply chain for Iranian medical tourism, and suggests resilience strategies for their prevention and improvements to the current situation. The participants were experts in the medical tourism supply chain chosen via purposive and snowball sampling. The results obtained via thematic analysis of interviews, as well as failure modes and effects analysis (FMEA) and failure analysis after occurrence (FAAO) techniques, led to identifying 75 risks which were classified into five major categories: supply, demand, internal, external and supply chain management risks. Additionally, a literature review and interview results revealed several resilience strategies categorized as pre-risk coping or post-risk recovery strategies for tackling the risks. Furthermore, the resilience number of the medical tourism supply chain increased from 0.4 (pre-risk occurrence) to 0.5 (post-risk occurrence). Implications and suggestions for future research are presented.